Monte Carlo simulation of detection of cirrus cloud properties by Micro Pulse Lidar - Cotturone, James A., Jr., author; Cox, Stephen K., author (Colorado State University. Libraries, 1996)
The development of the Micro Pulse Lidar (MPL) provides researchers with a system capable of continuous, eye-safe monitoring of atmospheric properties. The MPL operates with low energy, high pulse repetition frequency radiation in the visible portion of the spectrum. To investigate the interaction between visible radiation and atmospheric constituents, a model using Monte Carlo techniques has been refined to simulate MPL return profiles. An inherent feature of the MPL is its narrow receiver field of view (FOV) which is necessary to limit background noise. The effect of such a FOV and the role multiple scattering effects play in MPL operations are investigated in this study. Cloud base height and the radiative properties of cirrus clouds are important for determining the radiation budget of the planet. Inferred cirrus cloud radiative properties vary with the type of crystals assumed to compose the model clouds. To properly model optically thin clouds, it is important to include a standard background atmosphere composed of Rayleigh and aerosol scatterers. Its inclusion allows one to take advantage of information deduced from both the cloud and above cloud layer. Information that is unavailable when sampling optically thick clouds. This capability plays a pivotal role in an inversion algorithm that is developed and described. It is shown that the algorithm allows one to infer important cloud optical properties such as volume extinction coefficient, cloud optical depth, and isotropic backscatter to extinction ratio, also known as the lidar ratio. The algorithm shows that reliable results may be obtained from clouds of optical depth ranging from 0.05 to 1.4. For clouds of greater optical depth, it is shown that model "noise" causes results to become unstable. This instability is investigated and the sensitivity of algorithm results to the accuracy of essential parameters is examined. Calculations of the multiple scattering factor are also made for model clouds of varying optical depth.
May 1996.
Also issued as James A. Cotturone's thesis (M.S.) -- Colorado State University, 1996.
Keywords: Cloud physics -- Simulation methods; Cirrus clouds; Satellite meteorology; Monte Carlo method